Medicare I: Evaluation of Alternative Reform Measures - Eduardo T. Gonzalez; Corazon Urquico; Beringuela. Maria Luisa (Philippine Institute for Development Studies (PIDS), 1995)
This study seeks to provide the Philippines Medical Care Commission with short-run and long-run alternatives aimed at improving the performance of Medicare in terms of efficiency and equity. This bridges the findings of two baseline studies: Administrative Issues of Medicare I and Economic Evaluation of Medicare I.
Keywords: 330; medical care; efficiency issues; equity; simulation model; income; subsidy